The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1091/mbc.e16-12-0874
|View full text |Cite
|
Sign up to set email alerts
|

LET-99 functions in the astral furrowing pathway, where it is required for myosin enrichment in the contractile ring

Abstract: LET-99 is required for furrowing during cytokinesis in both symmetrically and asymmetrically dividing cells. This function is distinct from the role of LET-99 in spindle positioning with Gα signaling. LET-99 is localized to the furrow, where it acts to promote myosin enrichment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Prior work showed that let-99 ’s enhancement of the cytokinesis defects of centralspindlin mutants did not correlate with defects in spindle position or elongation (Bringmann et al, 2007; Price and Rose, 2017). Interestingly however, CED-10 is required for spindle orientation in certain cells of 8-cell embryo and later in the vulval lineage (Cabello et al, 2010; Kishore and Sundaram, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work showed that let-99 ’s enhancement of the cytokinesis defects of centralspindlin mutants did not correlate with defects in spindle position or elongation (Bringmann et al, 2007; Price and Rose, 2017). Interestingly however, CED-10 is required for spindle orientation in certain cells of 8-cell embryo and later in the vulval lineage (Cabello et al, 2010; Kishore and Sundaram, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the PAR polarity proteins restrict the localization of LET-99 to a lateral posterior band in asymmetrically dividing cells (Tsou et al, 2002; Wu and Rose, 2007). However, the localization of LET-99 to the prospective cleavage furrow is determined by the spindle and occurs in both asymmetrically and symmetrically dividing cells, and loss of LET-99 enhances the furrow ingression defects of zen-4 mutants in both types of cells as well (Bringmann et al, 2007; Price and Rose, 2017). Changes in the dynamics of cortical myosin have been reported for let-99 mutants, and let-99; zen-4 double mutants exhibit greatly reduced myosin accumulation at the furrow.…”
Section: Introductionmentioning
confidence: 99%
“…Three phases of ring closure have been defined, although it is not clear how flows influence these phases: 1) ring assembly, with little to no ingression of the membrane, followed by 2) furrow initiation, when the membrane is indented by the contractile ring, and 3) constriction, when the membrane ingresses until it reaches the midbody [e.g. (Chan et al, 2019;Khaliullin et al, 2018;Lewellyn et al, 2010;Osorio et al, 2019;Price & Rose, 2017)]. Parameters such as size and fate influence ring closure kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…First, the centralspindlin complex, which localizes both at the central spindle and at the adjacent equatorial cortex, activates myosin contractility through the regulation of the small GTPase Rho [3][4][5]. Second, astral microtubules prevent myosin activity at the pole of dividing cells, through mechanisms that remain to be precisely determined [6][7][8][9][10]. However, asymmetrically localized myosin also contributes to furrow localization [11][12][13].…”
Section: Introductionmentioning
confidence: 99%